Association study of miR‐149, miR‐196a2, and miR‐499a polymorphisms with coronary artery aneurysm of Kawasaki disease in southern Chinese population. (30th January 2022) - Fu, Lanyan; Xu, Yufen; Yu, Hongyan; Pi, Lei; Li, Jinqing; Zhou, Huazhong; Zhang, Li; Zhang, Tingfang; Che, Di; Gu, Xiaoqiong
Abstract: Background: Accumulating evidence suggests that several microRNA (miRNA) polymorphisms are closely associated with disease susceptibility or progression, such as in Kawasaki disease (KD). Our previous studies revealed the association of miR‐149 rs2292832 T>C and miR‐196a2 rs11614913 C>T polymorphisms with KD susceptibility. The present study further focused on the relationship between three miRNA polymorphisms ( miR‐149 rs2292832 T>C, miR‐196a2 rs11614913 C>T and miR‐499a rs3746444 A>G) and the risk of coronary artery aneurysm (CAA) in southern Chinese KD patients. Methods: We evaluated 318 KD patients with CAAs and 784 patients without CAAs. TaqMan assays were used to estimate genotyping and analyze the relationship between miRNA polymorphisms ( miR‐149 rs2292832 T>C, miR‐196a2 rs11614913 C>T and miR‐499a rs3746444 A>G) and risk associations of CAA by odds ratios (ORs) and 95% confidence intervals (CIs). Results: We found that the miR‐149 rs2292832 TC/CC genotype increased the CAA risk (adjusted OR = 1.53, 95% CI = 1.15–2.03, p  = 0.003 for TC, adjusted OR = 1.63, 95% CI = 1.08–2.47, p  = 0.021 for CC), whereas the miR‐499a rs3746444 AG genotype decreased the CAA risk in KD patients (adjusted OR = 0.33, 95% CI = 0.25–0.45 p  ≤ 0.001). Moreover, patients carrying two or three of these single nucleotide polymorphism (SNP) genotypes (rs2292832 TC/CC and rs11614913 TT and rs3746444 AA) had a higher risk for CAA than those who harbored only zero or one of these SNP genotypes. Conclusions: Our results demonstrated that the miR‐149 rs2292832 T>C polymorphism increased the risk of CAA in KD patients and that the miR‐499a rs3746444 A>G polymorphism decreased the risk of CAA in KD patients. Further studies with larger sample sizes and different centers are needed to confirm the findings of the present study. Abstract : Schematic diagram of the overall workflow.